The frequancy dependance of the fatigue fracture criterion - A. R. Arutyunyan; R. A. Arutyunyan (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
Some recent fatigue tests [1, 2] indicate that the fatigue curves have two fatigue limits. Experiments [3] also indicate the strong frequency dependence of the fatigue fracture process. These two effects are the main topics of the paper.
Keywords: Mechanics of particles and systems; Kinematics